Saxifraga hakkariensis (Saxifragaceae), a new species from Hakkâri province (Turkey) belonging to section Porphyrion - Firat, Mehmet (Phytotaxa, 2016)
A new species, Saxifraga hakkariensis (sect. Porphyrion), is described and illustrated from Hakkâri province, Turkey. From the morphological point of view, it appears to be similar to Saxifraga paniculata, but it differs in several morphological features including plant height, leaf and flower size. A comprehensive description of this species is provided, including detailed illustrations and photographs, geographical distribution, habitat and ecology, vernacular name and IUCN conservation status.